PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN MODEL PICTURE AND PICTURE DI KELAS III - Wilastri, Desi; Halidjah, Siti; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to determine the improvement of descriptive writing skill of students by used picture and picture model on grade III Elementary School 11 Semangak Bengkayang. The research method that been used was descriptive method. The type of this research was Classroom Action Research which had four steps. Those are planning, acting, observing and reflecting .This research was done in 3 cycles. The results of research were obtained (1) The ability of teacher to arrange learning draft from cycle I to cycle III were same, it was 3,54. The ability of teacher to do learning showed increase from cycle I 3,57, cycle II was 3,75, and cycle III was 3,86. The average of descriptive writing skill of students increased from cycle I with score 57,93 became 76,97 in cycle II and became 89,67 in cycle III. The using of picture and picture model increased the descriptive writing skill of students.Â Keywords : Descriptive Writing Skill, Picture and Picture Model.